2022
DOI: 10.1038/s41598-022-06118-6
|View full text |Cite
|
Sign up to set email alerts
|

A deletion at the polled PC locus alone is not sufficient to cause a polled phenotype in cattle

Abstract: Dehorning is a common practice in the dairy industry, but raises animal welfare concerns. A naturally occurring genetic mutation (PC allele) comprised of a 212 bp duplicated DNA sequence replacing a 10-bp sequence at the polled locus is associated with the hornless phenotype (polled) in cattle. To test the hypothesis that the 10 bp deletion alone is sufficient to result in polled, a CRISPR-Cas9 dual guide RNA approach was optimized to delete a 133 bp region including the 10 bp sequence. Timing of ribonucleopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This disagrees with a previous study that suggested a HAND1 binding site was altered by the 10‐bp deletion of P C (Nguyen et al, 2018). The knock‐out of a genomic region including these 10 bases resulting bovine fetuses were horned (Hennig et al, 2022). The overall evidence, therefore, suggests that P C does not interrupt an enhancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disagrees with a previous study that suggested a HAND1 binding site was altered by the 10‐bp deletion of P C (Nguyen et al, 2018). The knock‐out of a genomic region including these 10 bases resulting bovine fetuses were horned (Hennig et al, 2022). The overall evidence, therefore, suggests that P C does not interrupt an enhancer.…”
Section: Resultsmentioning
confidence: 99%
“…Nguyen et al (2018) mapped predicted bovine regulatory elements to the POLLED locus and found that the 10‐bp deletion of P C may interrupt a transcription factor binding site. However, when gene editing was used to knock out the 10‐bp deletion, the bovine fetuses remained horned (Hennig et al, 2022). This indicates that the 10‐bp deletion of P C is not responsible for the polled phenotype and that the 212‐bp duplication is likely to be the cause.…”
Section: Introductionmentioning
confidence: 99%
“…Mosaicism is a common problem observed when using genome editing reagents in developing embryos. Our previous work reported an inverse correlation between mosaicism rate and timing of injections hours post insemination (hpi), with the lowest mosaicism rates being seen in embryos edited 6 hpi 28 . Interestingly, we saw this same trend in the work presented here.…”
Section: Discussionmentioning
confidence: 97%
“…An issue with this strategy is that it has been well documented that microinjection of gene editing reagents into fish and mammalian zygotes results in progeny having more than two alleles (mosaicism), and often the frequency of these alleles is disproportionate and can vary across different tissues analyzed (Lamas-Toranzo et al 2019;Mehravar et al 2019;Hennig et al 2020Hennig et al , 2022. Mosaicism is typically the result of one or more of the following variables: (i) timing of nuclease injection (premeiotic, one cell, two cell), (ii) nuclease activity at intended target site, (iii) class of nuclease (Zinc Finger, Meganuclease, TALEN, Cas9, CPF1), (iv) reagents delivered (DNA, mRNA, protein), concentration, and associated half-life, and (v) target site accessibility in different cell types.…”
Section: Scaled Gene Modificationmentioning
confidence: 99%